INCIDENCE AND PATHOLOGY OF PARASITIC PNEUMONIA IN IRAQI LOCAL GOATS - H. Al-Joboury , K.; M. Al-Darraji, A. (The Iraqi Journal of Veterinary Medicine, 1990)
This study was designed to evaluate the incidence of caprine parasitic pneumonia and to characterize it's pathological (morphologic and histopathologic) features. Among a total of 800 examined goats, the incidence rate of the disease was 6.3%. Four types of parasitic pneumonia were reported: 1) chronic purulent and muco-purulent bronchopneumonia (52.94%), 2) chronic interstitial pneumonia (19.62%), 3) chronic granulomatous pneumonia (15.68%) and 4) chronic non-suppurative pneumonia (3.92%). Four miscellaneous parasitic lung lesions (7.84%) were also reported.